Suggested Teicoplanin as an anti-methicillin resistant staphylococcus aureus agent in infections of severely poisoned intensive care unit patients - Salimi, Alireza; Talaie, Haleh; Rezaie Hemami, Mohsen; Mahdavinejad, Arezou; Barari, Behjat Barari; Razi, Parmis; Kamalbeik, Sepideh (Acta Biomedica Atenei Parmensis, 2014)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) bacteraemia is related to high morbidity and mortality. Glycopeptide antibiotic is the choice of treatment in MRSA infections. Teicoplanin is a semi synthetic glycopeptide antibiotic with a spectrum of activity similar to vancomycin. Our objective is the evaluation of efficacy and safety of Teicoplanin in MRSA infections among severely poisoned intensive care unit (ICU) patients. Method: During a 6 months period, in a prospective cross sectional study 54 eligible patients from 80 clinically suspicious with MRSA infections were recruited. The efficacy and safety of Teicoplanin was evaluated 5 times. The clinical findings, laboratory data, and bacteriologic responses were defined as cure, improvement and failure. Results: The mean age of the patients was 36.3 years (range, 20-72, SD = 13.3). 75.9% were male. Suicidal attempts were recorded in 63%. The most common poisoning was TCAs, BZDs, tramadol and opium. 94.4% were unconscious and under mechanical ventilation. Tracheal cultures were positive in 98.1% by VAP diagnosis. Length of stay in the ICU was between 4-54 days. Total clinical effectiveness was 90.4%, and failure 9.6%. Mortality rate of the patient, was 9/54 (16.6 %) which 3 of them were for lack of a clinical response. On the fourth visit, the adverse effects included: rash (11.10%), anemia (36.17%), nephrotoxicity (17.02%) and thrombocytopenia < 150000 (100%). Other side effects such as: leucopenia, severe thrombocytopenia (< 50000), pancytopenia and red man syndrome were not detected. Conclusions: Teicoplanin is suggestible for MRSA infections among severely poisoned patients according to its efficacy, safety, half life and tolerance.